The hitchhiker’s guide to Australia: the 18,000-km-long journey of Alepia viatrix Jaume-Schinkel, Kvifte, Weele & Mengual, 2022 (Diptera, Psychodidae) discovered through citizen science - Santiago Jaume-Schinkel; Ximo Mengual; Andy G. Howe; Erinn P. Fagan-Jeffries (Check List, 2023)
The Neotropical genus Alepia Enderlein, 1937 (Diptera, Psychodidae) is newly recorded in Australia. We present new geographical records for Alepia viatrix Jaume-Schinkel, Kvifte, Weele & Mengual, 2022, extending the range of this species by 18,000 km. We attribute these new Australian records to the likely unintentional introduction of A. viatrix through international bromeliad trade. This moth fly was found by school children working with insect taxonomists through an Australian citizen-science project, Insect Investigators. We describe and present for the first time high-resolution SEM pictures of the eggs of the genus Alepia.